Program evaluation of English language learning for EYL curriculum development in Indonesia: teachers perception, challenges, and expectation - Metty Agustine Primary; Emi Emilia; Didi Sukyadi (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2023)
Program evaluation (henceforth PE) is a phase of curriculum development in the ELT context and is precious for improving curriculum reform. However, more research needs to be undertaken to investigate PE as a part of the English curriculum development for young learners context in Indonesian elementary schools. This case study research aims to scrutinize the teachers voices on PE centered on the challenges, perceptions, and expectations of the English to young learners (EYL) curriculum development. A semi-structured interview with three English teachers chosen by purposive sampling in Tasikmalaya, West Java, Indonesia, was employed to gather the data, and the collected data were examined thematically. The results showed that EYL teachers believe PE is vital to conduct since it can encourage curriculum development. They deal with challenges in designing and developing the curriculum related to lesson planning, materials development, instructional methods, and assessment practices. Teachers expected the EYL program to be adjusted with a suitable curriculum, such as contextualized, character-based, and school-based curricula. The study suggests that PE should be performed regularly to gain insightful reforms for the EYL curriculum, so teachers, schools, and stakeholders can advance the quality of the English program at Indonesian elementary schools.